A csehszlovák állam születése: Prága, 1918. október 28. - Tóth, Andrej (Acta Scientiarum Socialium, 2018)
There was no Czechoslovakian state at the outbreak of WW1. Apart from a few „dreaming emigrants„, no one thought in 1914 that such a state would ever come into existence. However, the Great War (1914â€’1918) enabled the birth of the Czechoslovakian state. On October 18, 1918, the national committee in Prague announced the foundation of the new state. Through the October 28 events in Prague and the decisions of Czech politicians, the paper presents the birth of the First Czechoslovakian Republic.